2021
DOI: 10.3390/ijerph19010365
|View full text |Cite
|
Sign up to set email alerts
|

Academic Performance during the COVID-19 Pandemic and Its Relationship with Demographic Factors and Alcohol Consumption in College Students

Abstract: The COVID-19 pandemic has caused many changes in the education sector worldwide, and school curricula have had to adapt to a non-face-to-face modality. However, international studies have concluded that this modality has affected the academic performance of students. The present study aimed to compare the academic performance of a sample of college students from before the start of quarantine with their current performance, and to test whether various demographic factors influenced these changes in conjunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The present study found that females more often than males reported high importance of good grades, satisfaction with studies, and above-average academic performance. These findings coincide with the results received by other authors showing that female students had a higher grade point average, failed fewer subjects and more often attended all course exams than male students [28,43]. Several factors can explain the difference in academic achievements between males and females, including substance use, which has been determined more often among male than female students [9,16,17,28].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study found that females more often than males reported high importance of good grades, satisfaction with studies, and above-average academic performance. These findings coincide with the results received by other authors showing that female students had a higher grade point average, failed fewer subjects and more often attended all course exams than male students [28,43]. Several factors can explain the difference in academic achievements between males and females, including substance use, which has been determined more often among male than female students [9,16,17,28].…”
Section: Discussionsupporting
confidence: 90%
“…In general, male students consume alcohol more frequently and in higher quantities than females [10,16,[27][28][29]. Our study found the differences in alcohol consumption between male and female students in 2000 and 2010 but not in 2017.…”
Section: Discussionmentioning
confidence: 42%
“…However, Sweden did not enforce restrictions such as shutdown or total isolation at home, suggesting that students in this study may have been less affected. One study found that the academic achievement improved during the pandemic, which could indicate a decrease in alcohol use since the study also found that high use of alcohol was associated with lower academic performance [ 49 ] and another found that alcohol use increased [ 50 ]. Based on these two studies, it is hard to ascertain how COVID-19 might have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on their child's gender, parents bring up differently, and this upbringing can affect a student's learning abilities, behavior, and habits toward school. Moreover, these differences in the treatment of the student are also taken into account by the teachers in the school, which affects the student's academic performance (Vargas-Ramos et al, 2021).…”
Section: Discussionmentioning
confidence: 99%